Efficient Restoration of the Dystrophin Gene Reading Frame and Protein Structure in DMD Myoblasts Using the CinDel Method - Jean-Paul; Dominique L Ouellet; Xavier Barbeau; Joël Rousseau; Pierre Chapdelaine; Patrick Lagüe; Jacques P Tremblay (Elsevier, 2016)
The CRISPR/Cas9 system is a great revolution in biology. This technology allows the modification of genes in vitro and in vivo in a wide variety of living organisms. In most Duchenne muscular dystrophy (DMD) patients, expression of dystrophin (DYS) protein is disrupted because exon deletions result in a frame shift. We present here the CRISPR-induced deletion (CinDel), a new promising genome-editing technology to correct the DMD gene. This strategy is based on the use of two gRNAs targeting specifically exons that precede and follow the patient deletion in the DMD gene. This pair of gRNAs induced a precise large additional deletion leading to fusion of the targeted exons. Using an adequate pair of gRNAs, the deletion of parts of these exons and the intron separating them restored the DMD reading frame in 62% of the hybrid exons in vitro in DMD myoblasts and in vivo in electroporated hDMD/mdx mice. Moreover, adequate pairs of gRNAs also restored the normal spectrin-like repeat of the dystrophin rod domain; such restoration is not obtained by exon skipping or deletion of complete exons. The expression of an internally deleted DYS protein was detected following the formation of myotubes by the unselected, treated DMD myoblasts. Given that CinDel induces permanent reparation of the DMD gene, this treatment would not have to be repeated as it is the case for exon skipping induced by oligonucleotides.